2014
DOI: 10.1002/2014je004698
|View full text |Cite
|
Sign up to set email alerts
|

Crater degradation on the lunar maria: Topographic diffusion and the rate of erosion on the Moon

Abstract: Landscape evolution on the Moon is dominated by impact cratering in the post-maria period.In this study, we mapped 800 m to 5 km diameter craters on >30% of the lunar maria and extracted their topographic profiles from digital terrain models created using the Kaguya Terrain Camera. We then characterized the degradation of these craters using a topographic diffusion model. Because craters have a well-understood initial morphometry, these data provide insight into erosion on the Moon and the topographic diffusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
330
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(351 citation statements)
references
References 57 publications
17
330
4
Order By: Relevance
“…In other words, the roughness signature of craters blends with the background with time. Smoothing of the rough ejecta blankets on the Moon occurs due to regolith formation and its gardening, which effectively mutes topography at scales of several hundreds of meters and shorter (Basilevskii, ; Craddock & Howard, ; Fassett & Thomson, ; Kreslavsky et al, ). On Vesta and Ceres, impact gardening cannot roughen their smooth ejecta blankets.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the roughness signature of craters blends with the background with time. Smoothing of the rough ejecta blankets on the Moon occurs due to regolith formation and its gardening, which effectively mutes topography at scales of several hundreds of meters and shorter (Basilevskii, ; Craddock & Howard, ; Fassett & Thomson, ; Kreslavsky et al, ). On Vesta and Ceres, impact gardening cannot roughen their smooth ejecta blankets.…”
Section: Discussionmentioning
confidence: 99%
“…The model ages were suggested to be consistent with those derived from crater densities, which were based on the lunar crater chronology model of Neukum et al []. The crater degradation models predicted that the maximum lifetime of a D = 200–300 m lunar crater was less than 3 Byrs, 800 Myrs for D = 150 m crater, and 70 Myrs for D = 20 m crater [ Fassett and Thomson , ]. If the 109 ± 4 and 800 ± 15 Myrs sample ages were true for Tycho and Copernicus, respectively, the melt pools on the crater rims should have D eq at least being 20 m and 150 m, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed D eq on these surfaces are much smaller (Table 1). Therefore, either the real ages of Tycho and Copernicus are substantially less than the prevalent sample ages and the crater chronology model of Neukum et al [] may have indicated larger than real ages for a given crater population, or that the crater degradation models may have overestimated the surface erosion rate on the Moon due to the possibly nonlinear topographic degradation rates for craters larger and less than 800 m diameter [ Fassett and Thomson , ]. The former, however, is disproved by recent work by Werner and Medvedev [] and Werner et al [].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the straight relationship formulated by Basilevsky (1976), TMa =2.5*D, (TMA is time in Ma and D is crater diameter in meters) the small secondary craters excavated by the surge should all but eroded long ago (~50 Ma lifetime for the 20 m fraction, or ~70 Ma, Fassett and Thomson, 2014). Given that the event is estimated at ~110 Ma (Arvidson et al 1976), the crater count should have approached the background level by now.…”
Section: Discussionmentioning
confidence: 99%